Litteraturen og revolutionen - Trotskij, Lev (Passage - Tidsskrift for litteratur og kritik, 2010)
Lev Trotskij: "Litteraturen og revolutionen" Abstract Lev Trotskij: “Literature and Revolution: Introduction” Leo Trotsky’s introduction to his Literature and Revolution from 1923 outlines the argument of the book: The revolution necessitates a unification of poetical experiments and political commitment. In opposition to the futurist idea of a complete break with the past, this necessity does not for Trotsky imply severing the ties to the so-called bourgeois literature of the nineteenth century, but a living, historically conscious dialogue with the past.